Delays in lymphatic filariasis elimination programmes due to COVID-19, and possible mitigation strategies - Prada, JM; Stolk, WA; Davis, EL; Touloupou, P; Sharma, S; Muñoz, J; Caja Rivera, RM; Reimer, LJ; Michael, E; de Vlas, SJ; Hollingsworth, TD (Oxford University Press, 2021)
Background: In view of the current global coronavirus disease 2019 pandemic, mass drug administration interventions for neglected tropical diseases, including lymphatic filariasis (LF), have been halted. We used mathematical modelling to estimate the impact of delaying or cancelling treatment rounds and explore possible mitigation strategies.